Influence of A-Site Modifications on the Properties of La0.21Sr0.74-xCaxTi0.95Fe0.05O3-delta Based Fuel Electrode for Solid Oxide Cell - Paydar S; Kooser K; Möller P; Volobujeva O; Granroth S; Lust E; Nurk G (ELECTROCHEMICAL SOC INC, 2025)
To make solid oxide fuel cell (SOFC) systems commercially attractive it's essential to reduce manufacturing cost and improve the stability of membrane electrode assembly (MEA). In this research, the influence of A-site modification on electrical and electrochemical performance of 5% A-site deficient La0.21Sr0.74-xCaxTi0.95Fe0.05O3-delta (x = 0.26 - 0.69) (LSCTF5-x) hydrogen electrode has been studied. Results indicate that the magnitude of A-site deficiency and Ca concentration in A-site influence the conductivity, catalytic activity and stability of the electrodes considerably. The highest stability was observed in the case of La0.21Sr0.26Ca0.48Ti0.95Fe0.05O3-delta anode composition. The maximal total electrical conductivity of porous electrode layer made of LSCFT5-x was 3.5 S cm(-1) at 850 degrees C characteristic of the La0.211Sr0.26Ca0.48Ti0.95Fe0.05O3-delta material in 97% H-2 + 3% H2O atmosphere. The best electrochemical performance was observed in the case of La0.21Sr0.37Ca0.37Ti0.95Fe0.05O3-delta , which showed polarization resistance value equal to 0.44 omega cm(2) after 100 h of stabilization at 800 degrees C in humidified (1.7% H2O) H-2 atmosphere. During the stability test the fuel cell with optimal anode composition 50 wt% La0.21Sr0.26Ca0.48Ti0.95Fe0.05O3-delta + 50 wt% Ce0.9Gd0.1O2-delta showed power density of 437 mW cm(-2) at 850 degrees C in 98.3% H-2 + 1.7% H2O atmosphere.